Does bimanual coordination training benefit inhibitory function in older adults? - Torre, Marta Maria; Langeard, Antoine; Alliou, Louis; Temprado, Jean-Jacques (Frontiers in Aging Neuroscience, 2023)
Studies investigating complex movement training benefits on inhibitory functions and the transfer to non-practiced motor and cognitive tasks are scarce. The present experiment addressed this issue thanks to a bimanual coordination paradigm. Results confirmed that training delayed the spontaneous transition frequency. They also showed that bimanual coordination training transferred to the untrained bimanual coordination task since it involved inhibition function to switch from one pattern to the other. Performance improvement was also observed for the two untrained cognitive tasks. Mediation analyses confirmed that the transfer of training in both the motor and cognitive tasks was mediated by the enhancement of inhibition.